The Relationship Between Authentic Leadership and Employee Creativity in Service Sector - Noor Afifah Atan; Eta Wahab (Research in Management of Technology and Business, 2024)
Malaysia is falling behind in innovations study level though there are innovative activities going on. Hence, there is an urgent need to ensure service sector in Malaysia could continue for the growth of Malaysian’s GDP. The objective of this study is to determine the level of authentic leadership, to determine the level of employee creativity and to identify the relationship between authentic leadership and employee creativity. A quantitative approach has been applied in this study. The study was conducted through the distribution of online survey among 214 employees in the service sector in Kulai, Johor with a response rate of 67.2%. The data collected from the study had been analyzed using both descriptive and correlation analysis by SPSS. The study revealed that there is no relationship between authentic leadership and employee creativity in the service sector.